Mental Health in Young Adults: The Impact of the COVID‐19 Pandemic - Carneiro, Luísa (2022)
Introduction: When we talk about young adults we tend to consider them as a population in good health. However, in recent times, the transition from adolescence to adulthood has been the focus of attention to implement strategies for health promotion and disease prevention. The aim of this study was to understand the health status of a young adult population attending higher education and, in what way, the pandemic by COVID‐19 had an impact on the different dimensions of daily life, namely on well‐being and mental health. Methods: A questionnaire was applied and disseminated electronically by young people in university education and 149 responses were obtained. Results: The students showed some feelings of low personal fulfilment (28% say they feel unfulfilled), feelings of loneliness (26% say they feel alone), feelings of depression (42% say they feel depressed), lack of confidence in themselves (17%) and in some cases feel that their energy levels are low or extremely low (26%).The pandemic context brought several challenges to young adults who had difficulty making new friends (94%), the perception of feelings of nervousness, anxiety or tension during confinement was reported by 51% of students and the inability to control their concerns or emotions was reported by 43%. Conclusion: Several studies report mental changes that can develop or worsen after traumatic events such as a pandemic, and the results of our study are in line with this evidence. Feelings of nervousness, tension and anxiety, as well as difficulty in controlling emotions, emerged in association with the pandemic, emphasizing the need to develop health strategies that respond to these emerging needs.